The Social Criticisms of Rah(i)m Poetry by Kedung Darma Romansha - Alfadlilah, Muna (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2023)
An expressing media with literature work could indirectly convey various social criticisms toward a certain phenomenon. The most frequently occurring social criticism is the social reality portrayal of a community. This study aims to describe the form of social criticism contained in the poetry entitled Rahi(i)m by Kedung Darma Romansha. Using qualitative methods and a literary sociology approach, especially social criticism, this study reveals the author's worldview of phenomena that occur in society. The study results show that the author of poetry criticises social situations, namely: the author's criticism of poverty, crime, family disharmony, juvenile delinquency, violation of norms, and environmental problems. Social criticism also reveals the author's disappointment, annoyance, anger, and regret towards the arrogant and unfair performance of government officials in responding to socio-cultural problems that occur in society.